A social media analysis of students’ perspective toward online learning during the COVID-19 pandemic - Kanetasya Sabilla; Romi Bhakti Hartarto (Cogent Social Sciences)
During the spread of coronavirus disease 2019 (COVID-19) worldwide, many countries have instructed the shutdown of all educational facilities to break the chain of virus transmission. Since March 2020, approximately 45 million students in Indonesia have adapted to online learning due to the COVID-19 pandemic. This study aimed to analyze Indonesian students’ perceptions of online schools using social media data, specifically Twitter. Based on the search query, there were 12,243 tweets collected from the Netlytic software from March 1st to 31st, 2021. From this social media platform, we found that students did not experience good things in an online school. Some of them might enjoy online school, but most of the students felt that it had a negative impact on them. In the word-level sentiment analysis, 1,649 words (81.59%) were considered negative words; for example, students frequently complained about how they felt ‘lazy’, ‘tired’, and ‘bored’. Meanwhile, the remaining 372 words (18.41%) were considered positive words as the students expressed their feelings with words like ‘comfortable’, ‘thanked God’, and ‘good’. Based on this finding, we suggest that educational facilitators prepare to adjust course materials and delivery to improve students’ online learning experiences.